2007
DOI: 10.1177/1533317506297517
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychopathologic Response to Rivastigmine in Dementia With Lewy Bodies Compared to Alzheimer’s Disease: A Case Control Study

Abstract: Cholinesterase inhibitors (ChEIs) are effective in improving cognition and behavior in patients affected by Alzheimer's disease (AD) as well as by Lewy bodies dementia (DLB). The authors compared the effect of rivastigmine in the treatment of cognitive impairment and behavioral and psychological symptoms of dementia (BPSD) in 30 AD and in 30 DLB patients. At baseline, DLB compared to AD patients showed a greater number of extrapyramidal symptoms (P < .005) and were similar regarding cognitive symptoms and BPSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In particular, the different personality traits [37] , the presence of hallucinations, sleep disturbances and extrapyramidal signs, included in the core features of LBD [38,39] , would suggest that Lewy body pathology might be a contributing factor to the clinical profile of naMCI.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the different personality traits [37] , the presence of hallucinations, sleep disturbances and extrapyramidal signs, included in the core features of LBD [38,39] , would suggest that Lewy body pathology might be a contributing factor to the clinical profile of naMCI.…”
Section: Discussionmentioning
confidence: 99%
“…MCI subjects in the present study showed a heterogeneous pattern of disturbances in different cognitive areas, in psycho-behavioral symptoms and in motor and neurological signs, suggesting that MCI may be the earliest clinical manifestation of different age-related neurological diseases, each one associated with different clinical phenotypes at the stage of MCI. The association between mild EPS and specific behavioral disturbances (anxiety, depression, apathy and sleep disturbances) included in the core features of dementia with Lewy bodies (DLB;McKeith et al, 2005;Rozzini et al, 2007) would suggest that Lewy body pathology might be the major contributing factor to both EPS and BPSD. Strengthening this hypothesis are the neuropsychological data that highlight a correlation between severity of EPS and visuospatial skills, which are generally compromised in DLB (Cummings, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…10 The other pharmacological interventions may have beneficial effects on the persons' cognitive functions and psychiatric symptoms but not necessarily on their performance of self-help and other basic daily living activities. [10][11][12][13][14][15][16] Behavioral intervention can embrace a variety of strategies frequently directed at practicing memorybased activities. Among the most common strategies, one can find reality orientation therapy (in which practical information such as the patient's name, time, date, location, and current events are consistently rehearsed), attention and memory exercises (in which the patients are led to focus on specific attention and memory tasks), as well as face-name association tasks.…”
mentioning
confidence: 99%